Asymptomatic congenital intrahepatic portosystemic shunt - E. A. Sidorov; P. M. Zelter; D. V. Solovov; А. А. Manukyan (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
Spontaneous asymptomatic intrahepatic portosystemic shunt is a rare anomaly of the hepatic vasculature. The main clinical manifestations may be encephalopathy, bleeding or hyperinsulinism, due to the constant shedding of blood. This article presents a case of an asymptomatic congenital intrahepatic portosystemic shunt, found in patient I., aged 25, with the results of various imaging methods, as well as an analysis of the main types of the described vascular anomaly.